Discriminating features of gait performance in progressive supranuclear palsy. Issue 8 (August 2015) - Amano, Shinichi; Skinner, Jared W.; Lee, Hyo Keun; Stegemöller, Elizabeth L.; Hack, Nawaz; Akbar, Umer; Vaillancourt, David; McFarland, Nikolaus R.; Hass, Chris J.
Abstract: Introduction: Progressive supranuclear palsy (PSP) is the most common form of atypical Parkinsonism; however it is underdiagnosed and often misdiagnosed as Parkinson's disease (PD). Methods: We investigated gait initiation (GI) and gait performance in a total of 36 participants (12 PSP, 12 PD and 12 healthy age- and gender-matched controls) to gain further insight into specific motor deficits that characterize dynamic postural control and gait in PSP. Anticipatory postural adjustments (APAs), quantified by center of pressure (COP) displacement and speed prior to an initial heel off, and the maximum distance (COPCOM) between COP and center of mass (COM) during all three GI phases were calculated to evaluate dynamic postural control. Steady-state gait performance was also evaluated and compared across the groups. Results: APAs in PSP were significantly altered such that the posterior COP shift is profoundly diminished when compared to PD (p < 0.05). Moreover, proper velocity control during GI in PSP was affected, particularly in the mediolateral direction, when compared to PD (p < 0.05). The diminished COPCOM distance is further indicative of more severe dynamic postural instability in PSP than in PD (p < 0.05). Significant differences in spatiotemporal parameters, inter-step variability, and asymmetry during gait in PSP, in comparison with PD were also identified (all p's < 0.05). Conclusion: The present study reveals that the compensatory GI strategy in PSP is distinct from PD and paradoxically induces lateral instability. Further, gait performance in PSP is slower and more variable which could be the consequence of lateral instability and fear of falling. Highlights: Gait initiation (GI)/gait in Progressive Supranuclear Palsy (PSP) were evaluated. PSP more severely altered GI strategy than Parkinson's Disease (PD). Unlike PD, PSP affected spatial/temporal aspects of gait, prioritizing stability over mobility. PSP gait may be a compensatory consequence to their lateral instability.